Collaborative learning in the professional development of medical radiation practitioners. Issue 2 (18th September 2021) - Turner, Michelle; Morasi, Sanya; Mrsnik‐Hamdi, Monica; Shanahan, Madeleine
Abstract: Introduction: Medical radiation practitioners (MRPs) participate in continuous professional development (CPD) to update their knowledge, skills, safety standards and patient care. The Medical Radiation Practice Board of Australia (MRPBA) recommends that practitioners participate in a variety of activities and to incorporate the use of collaborative learning tools. The aim of this research was to investigate the value, use and workplace supports for online and face‐to‐face collaborative learning for CPD. Methods: A cross‐sectional online survey of Australian MRPs was conducted. The questionnaire was distributed via e‐blast from the Australian Society of Medical Imaging and Radiation Therapy (ASMIRT) to members. Results: A total of 115 completed questionnaires were received. Seminars, workshops and conferences were the most valued collaborative learning tools, with no significant difference in ranking observed ( P > 0.05). The majority of MRPs regularly attend conferences (64%, n = 73) with those working in a metropolitan location more likely to attend. MRPs are supported by their workplace to attend conferences through the provision of paid leave (61%, n = 63), funding (50%, n = 52) and to a lesser extent travel expense (38%, n = 39). More than half (60%, n = 69) of the participants use social media for CPD with Facebook being the most frequently used and most useful online platform. The most common reasons for using social media for CPD were accessibility to information (85%, n = 56), little geographical limitations (77%, n = 51) and ease of use (74%, n = 49). Conclusion: Medical radiation practitioners currently utilise both face‐to‐face and online collaborative learning tools to meet their CPD needs. Face‐to‐face tools are more frequently utilised and highly valued by MRPs. Abstract : To maintain registration with the Australian Health Practitioner Regulation Agency (AHPRA) medical radiation practitioners (MRPs) must participate in continuous professional development (CPD). Seminars, workshops and conferences were ranked by MRPs the most valued collaborative learning tools and no significant difference was indicated ( P > 0.05).